Development of a Direct Compression Excipient from Epichlorohydrin-Crosslinked Carboxymethyl Rice Starch with Sodium Silicate Using a Coprocessing Technique - Karnkamol Trisopon (2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim A new, free-flowing tablet disintegrant based on a coprocessed, cross-linked carboxymethyl rice starch (CXO) is developed using a combination of chemical and physical modifications. Cross-linked carboxymethyl starches are synthesized from an etherification between native rice starch and monochloroacetic acid and a cross-linking reaction with epichlorohydrin with various ratios of the etherification reaction time to the cross-linking reaction time (1:1, 1:0.67, and 1:0.33). The modified starches are then coprecipitated with 0–25% sodium silicate solution in methanolic solvent to obtain the CXOs. The physicochemical properties of the CXOs are characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, X-ray diffractometry, and differential scanning calorimetry. The solubility, swellability, moisture sorption capacity, and flowability parameters are also investigated and compared with those of native starch. A 10% sodium silicate solution is found to be best suited for coprocessing, yielding a modified starch (CXO-12) with excellent flowability and compressibility. The lubricant sensitivity ratio of CXO (0.13) is 4–6 times lower than those of sodium starch glycolate (SSG) and croscarmellose sodium (CCS), and its dilution potential (11.2% w/w) is the best among the three excipients. The disintegration times of the model drug tablets containing CXO (16.83 ± 3.19 s) are not significantly different from those containing SSG (14.00 ± 2.45 s) or CCS (14.00 ± 2.83 s). A dissolution study showed that the drug release is greater than 80% after 15 min in the medium. These results suggest that CXO could be applied as a free-flowing super disintegrant for direct compression processes.